DAMPAK PSIKOLOGIS KURANGNYA PERAN AYAH (FATHERLESS) PADA PEREMPUAN DEWASA AWAL: STUDI FENOMENOLOGIS - Musthofa, M. Hanif; Arfensia, Danny Sanjaya (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2024)
Fathers have an important role in the family, in addition toearning a living, fathers must also provide good parentingto their children, especially women. However, if this role islacking or even absent, it will have a psychological impacton the development and growth of children. Fatherless orlack of father's role in the child's life can be in the form ofphysical, psychological, and emotional absence. Thepurpose of this study is to determine the psychologicalimpact experienced by women in early adulthood whoexperience fatherlessness. This research usesphenomenological qualitative methods. The participantswere two people aged 20 and 21 years, early adult women,and experienced fatherlessness such as divorce andinfidelity. Data were collected using semi-structuredinterviews, then analyzed using thematic analysis method.The results of this study found four main themes, namely 1)worry about the future, 2) the psychological impact offatherless, 3) affecting self-esteem, 4) seeking the support ofothers. Fatherless has a significant psychological impact onparticipants. It can be concluded that the role of father isneeded for early adult women to provide direction, as a rolemodel, increase self-confidence, and build good self-esteem.